1998
DOI: 10.1002/(sici)1097-0290(19980705)59:1<68::aid-bit9>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water and enzyme concentration on thermolysin-catalyzed solid-to-solid peptide synthesis

Abstract: We have studied a thermolysin‐catalyzed solid‐to‐solid dipeptide synthesis using equimolar amounts of Z‐Gln‐OH and H‐Leu‐NH2 as model substrates. The high substrate concentrations make this an effective alternative to enzymatic peptide synthesis in organic solvents. Water content was varied in the range of 0 to 600 mL water per mol substrate and enzyme concentration in the range of 0.5 to 10 g/mol of substrates. High yields around 80% conversion and initial rates from 5 to 20 mmol s−1 kg−1 were achieved. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…However, water is essential for proteases; mixed aqueous media usually reduce enzyme activity considerably, and insufficiently hydrated catalyst can even be completely inactive. [80][81][82][83] The major limitations of enzyme-mediated transamidation are the high substrate selectivity of the catalyst that may bias the reaction and the fact that the equilibrium typically lies on the side of the starting materials (acids and amines). This latter drawback can be eliminated by using an organic cosolvent in the presence of a hydrophilic solid phase.…”
Section: Scheme 4 Reversible Transesterification To Effect Acyl Migrmentioning
confidence: 99%
“…However, water is essential for proteases; mixed aqueous media usually reduce enzyme activity considerably, and insufficiently hydrated catalyst can even be completely inactive. [80][81][82][83] The major limitations of enzyme-mediated transamidation are the high substrate selectivity of the catalyst that may bias the reaction and the fact that the equilibrium typically lies on the side of the starting materials (acids and amines). This latter drawback can be eliminated by using an organic cosolvent in the presence of a hydrophilic solid phase.…”
Section: Scheme 4 Reversible Transesterification To Effect Acyl Migrmentioning
confidence: 99%
“…After 15 min, the dry enzyme powder was added straight from the bottle. The complete reaction mixture was then mixed and separated into individual samples as previously described (Erbeldinger et al, 1998a). Each reaction mixture contained (unless otherwise stated) 2 mmol of both substrates, 200 L water, and 10 mg thermolysin or 300 mg Thermoase P160.…”
Section: Enzymatic Reactionsmentioning
confidence: 99%
“…These results were notably lower than those obtained at 0.15 mmol (70% yield and 96% conversion). Erbeldinger et al (1998) reported that in solid-to-solid biotransformations there is an optimal buffer or solvent content for each reaction. On this basis, we considered the possibility that the optimal mL ethanol/mol substrate ratio could be different, depending on the amount of substrate.…”
Section: Two-step Synthesismentioning
confidence: 99%